New identification and significance of Early Cretaceous mafic rocks in the interior South China Block - Hui-Min Su (Nature Portfolio, 2021)
Abstract Early Cretaceous mafic rocks are first reported in the northern Guangxi region from the western Qin-Hang belt in the interior South China Block. A systematic investigation of zircon U–Pb dating, whole-rock geochemistry, Sm–Nd isotopes and zircon Hf–O isotopes for these mafic rocks reveals their petrogenesis and the mantle composition as well as a new window to reconstruct lithospheric evolution in interior South China Block during Late Mesozoic. Zircon U–Pb dating yielded ages of 131 ± 2 Ma to 136 ± 2 Ma for diabase and gabbro from Baotan area, indicating the first data for Early Cretaceous mafic magmatism in the western Qing-Hang belt. These mafic rocks show calc-alkaline compositions, arc-like trace element distribution patterns, low zircon εHf(t) of − 9.45 to − 6.17 and high δ18O values of + 5.72 to + 8.09‰, as well as low whole-rock εNd(t) values of − 14.27 to − 9.53. These data suggest that the studied mafic rocks are derived from an ancient lithospheric mantle source that was metasomatized during Neoproterozoic subduction. Thus, the occurrence of these mafic rocks indicates a reactivation of Neoproterozoic subducted materials during an extension setting at Late Mesozoic in the western Qin-Hang belt, an old suture zone that amalgamates the Yangtze and Cathaysia blocks.